A history into genetic and epigenetic evolution of food tolerance: how humanity rapidly evolved by drinking milk and eating wheat. Issue 6 (December 2017) - Blanchard, Carine
Abstract : Purpose of review: Human exposure to wheat and milk is almost global worldwide. Yet the introduction of milk and wheat is very recent (5000–10 000 years) when compared to the human evolution. The last 4 decades have seen a rise in food allergy and food intolerance to milk and wheat. Often described as plurifactorial, the cause of allergic diseases is the result from an interplay between genetic predisposition and epigenetic in the context of environmental changes. Recent findings: Genetic and epigenetic understanding and their contribution to allergy or other antigen-driven diseases have considerably advanced in the last few years. Yet, environmental factors are also quite difficult to identify and associate with disease risk. Can we rethink our old findings and learn from human history and recent genetic studies? Summary: More than one million years separate Homo habilis to today's mankind, more than 1 million years to develop abilities to obtain food by foraging in diverse environments. One million year to adjust and fine-tune our genetic code and adapt; and only 1% of this time, 10 000 years, to face the three biggest revolutions of the human kind: the agricultural revolution, the industrial revolution and the postindustrial revolution. With big and rapid environmental changes come adaptation but with no time for fine-tuning. Today tolerance and adverse reactions to food may be a testimony of adaptation successes and mistakes.